Limites e possibilidades do uso da aprendizagem baseada em equipes (ABE) pelo professor de Ciências da Natureza e Biologia na Educação Básica - Lousan, Nathalie Emanuelle Pigoretti [UNIFESP] (2020)
All activities included in the educational process are known to be influenced by the teacher's self-efficacy belief. Therefore, given the challenges of pedagogical practice and the current historical structure of Brazilian education, I consider teacher empowerment not only necessary but also a welcome condition. Given this reality, the objective of this study was to enable science and biology teachers to apply the TBL in their daily school life, to know the relationship between the use of this strategy and teacher self-efficacy and to evaluate its effectiveness in basic education. It was an exploratory study with qualitative profile. Teachers were offered a training in TBL and at the end they were instructed to apply such a strategy in their classrooms. For data collection, the participating teachers answered the Sociodemographic and Professional Practice Questionnaire, the Teaching Self-Efficacy scale and a semi-structured Interview entitled “Evaluating TBL”. In the organization of the data collected through the interviews, the Collective Subject Discourse (CSD) and the word cloud were used. For analysis was used Content Analysis (CA), thematic analysis (TA). They completed the training and applied the TBL in their school daily 6 teachers. The contribution of this strategy was verified with the significant and collaborative learning of the students of the basic education, even with the initial difficulty of the teachers in assembling the work teams in accordance with the assumptions of the methodology. In general, there was a higher perception of teacher self-efficacy after the formation and application of TBL. With this study, we observed the contributions of the use of TBL to the meaningful and collaborative learning of students of basic education, and how this active teaching strategy can be a tool of empowerment and teacher empowerment, contributing to increase their perception of self-efficacy, engagement and job satisfaction.